Ossicular Chain Erosion During Chronic Otitis Media - Saboor, Halla; Afridi, Habib ur Rehman; Muhammad Tariq (Indus Journal of Bioscience Research, 2025)
Background: Chronic otitis media (COM) is a significant cause of ear-related morbidity and often leads to complications such as ossicular chain erosion (OCE), which contributes to hearing loss and reduced quality of life. This study aims to determine the prevalence of OCE in patients with COM and its association with demographic and clinical factors. Methods: This descriptive cross-sectional study was conducted in the Department of ENT at Lady Reading Hospital, Peshawar, over a six-month period from 1st November 2021 to 1st April 2022. A total of 171 patients with COM were selected using non-probability consecutive sampling. Data collection involved detailed medical histories, physical examinations, audiometric evaluations, and surgical confirmation of OCE. Statistical analysis was performed using SPSS version 21, with stratification and chi-square tests to identify significant associations. Results: The prevalence of OCE among the study population was 15.20%. Age and duration of COM were significantly associated with OCE, with older patients and those experiencing prolonged disease showing higher prevalence rates (p < 0.05). Gender did not have a statistically significant impact on OCE prevalence. Audiometric findings confirmed the role of OCE in conductive hearing loss. Conclusion: OCE is a significant complication of COM, particularly in patients with prolonged disease duration and advanced age. Early diagnosis, regular monitoring, and timely surgical intervention are critical to reducing the risk of hearing impairment. These findings underscore the need for increased public awareness and improved access to ENT care to prevent and manage complications associated with COM.